The development of a framework to evaluate the organisational and policy impacts of the Community Health Information Tracking System (CHITS) in the Philippines - Premji, Shainur; ProQuest Dissertations and Thesis (Ann Arbor University of Calgary (Canada), 2010)
The Community Health Information Tracking System (CHITS) is an electronic health information system developed in 2004 to address weaknesses of the current manual data collection system in the Philippines. Although believed to have improved data accuracy, integrity and decision-making at the community level, a formal evaluation has not taken place. This study assesses the organisational and policy impacts of CHITS and develops a framework for its formative evaluation. Field research took place between March and July 2008. Results indicate benefits at the individual end-user level. Workers are empowered, having learnt to use a computer for the first time. The policy impacts are mixed; support is necessary from higher-level authorities to help make CHITS a sustainable application. The Organisational/Policy Implementation and Sustainability Framework is an evidence-based tool created from the study findings to help local stakeholders evaluate CHITS and improve it as it is being expanded.
Includes bibliographical references.
Electronic reproduction.
Keywords: Public administration; Information science; Health care management